(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Skin disorders are major health issues in the present era. It is a multifaceted concept that includes the emotional, social, and economic impacts on individuals, their families, and society as a whole. As per Ayurveda, all skin disorders come under the broad term "Kushta" which is further divided into Mahakushta and Kshudra kushta. Mandala kushta which is described as one of the Mahakushtha finds similarity with psoriasis. Aim: The aim was to evaluate the efficacy of Virechana karma (purgation) and Shaman aushadhi in Mandal kustha. Material and Method: A 20-year-old female patient was presented with complaints of reddish-white lesion on behind left ear, bilateral upper and lower limbs and back region associated with including severe itching, sometimes bleeding from lesions on itching, burning sensation and white silvery scaling. She was treated with Shodhanartha Snehapana with Panchatikta Ghrita followed by Sarvanga Abhyanga with Neem taila and Sarvanga Swedana. She was given Virechana with Triphala Kwatha, Trivrita avaleha and Draksha kwatha. The Shamana Chikitsa included Gandhak rasyana - 250mg, Kaishor guggulu - 1gm, Panchtikta ghrita guggulu 1gm, Brihat dantaphala taila for L/A for 1 month. Result: The results of the treatment are recorded as a photographic document. As per the result lesions of the skin became lighter in colour and scaling was completely gone. Conclusion: With the help of Ayurvedic treatment we can completely cure this disease with proper medication and diet management.